Case Report: Histopathology and Prion Protein Molecular Properties in Inherited Prion Disease With a De Novo Seven-Octapeptide Repeat Insertion - Cali, Ignazio; Cracco, Laura; Saracino, Dario; Occhipinti, Rossana; Coppola, Cinzia; Appleby, Brian Stephen; Puoti, Gianfranco (Frontiers in Cellular Neuroscience, 2020)
The insertion of additional 168‐base pair containing seven octapeptide repeats in the prion protein (PrP) gene region spanning residues 51 to 91 is associated with inherited prion disease. In 2008, we reported the clinical features of a novel de novo seven-octapeptide repeat insertion (7-OPRI) mutation coupled with codon 129 methionine (M) homozygosity in the PrP gene of a 19-year-old man presenting with psychosis and atypical dementia, and 16-year survival. Here, we describe the histopathological and PrP molecular properties in the autopsied brain of this patient. Histopathological examination revealed widespread brain atrophy, focal spongiform degeneration, cortical PrP plaques, and elongated PrP formations in the cerebellum. Overall, these histopathological features resemble those described in a Belgian pedigree with 7-OPRI mutation except for the presence of PrP plaques in our case, which are morphologically different from the multicore plaques described in some OPRI mutations and in Gerstmann-Sträussler-Scheinker syndrome. The comparative characterization of the detergent- soluble and -insoluble PrP in our patient and in sporadic Creutzfeldt-Jakob disease revealed distinct molecular signatures. Proteinase K digestion of the pathogenic, disease-associated PrP (PrPD), revealed PrPD type 1 in the cerebral cortex and mixed PrPD types 1 and 2 in the cerebellum. Altogether, the present study outlines the importance of assessing the phenotypical and PrP biochemical properties of these rare conditions, thereby widening the spectrum of the phenotypic heterogeneity of the 7-OPRI insertion mutations. Further studies are needed to determine whether distinct conformers of PrPD are associated with two major clinico-histopathological phenotypes in prion disease with 7-OPRI.